The Production and Characterization of Seashell Reinforced Epoxy Composite Material - Aydın, Cihat; Avcı, Sinan (Niyazi BULUT, 2023)
In this study, it was aimed to examine the production, characterization and mechanical properties of epoxy matrix composites added with seashells collected from different coastal locations of the Mersin Region, which is a natural raw material. Natural seashells with different mass ratios were ground into different sizes and added into epoxy, the matrix material. By performing physical and chemical characterization of the produced composites, the next step is to analyze and produce the product with the best and most superior properties.
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri